2021 4th IEEE International Conference on Industrial Cyber-Physical Systems (ICPS) 2021
DOI: 10.1109/icps49255.2021.9468266
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Asset Administration Shells in Industry 4.0: A Survey

Abstract: The Asset Administration Shell (AAS) is a fundamental concept in the Reference Architecture Model for Industry 4.0 (RAMI 4.0), that provides a virtual and digital representation of all information and functions of a physical asset in a manufacturing environment. Recently, Semantic AASs have emerged that add knowledge representation formalisms to enhance the digital representation of physical assets. In this paper, we provide a comprehensive survey of the scientific contributions to Semantic AASs that model the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…For examples, the physical decomposition is differently expressed by several standards, like the ISO 14224, ISO 15926, and IEC 62264, used to develop AAS (Asset Administration Shell). However, it is already demonstrated that the maintenance-related terms urge effort to be syntactically and semantically consistent [36,49]. Thus, MOCA extensively relies on BFO-compliant ontologies, and, in case of missing or contradicting formalisations, a look to international standards is given; ultimately, a look towards the vocabulary already used by the food company in which the ontology is verified is given to resolve incompliances.…”
Section: Ontology Development Methodology and Design Choicesmentioning
confidence: 99%
“…For examples, the physical decomposition is differently expressed by several standards, like the ISO 14224, ISO 15926, and IEC 62264, used to develop AAS (Asset Administration Shell). However, it is already demonstrated that the maintenance-related terms urge effort to be syntactically and semantically consistent [36,49]. Thus, MOCA extensively relies on BFO-compliant ontologies, and, in case of missing or contradicting formalisations, a look to international standards is given; ultimately, a look towards the vocabulary already used by the food company in which the ontology is verified is given to resolve incompliances.…”
Section: Ontology Development Methodology and Design Choicesmentioning
confidence: 99%
“…In [63], the authors design and propose an AAS model for predictive maintenance. Moreover, in [64], the authors provided a comprehensive survey of AAS models for the information and communication layer, where they presented some ontologies used for scheduling, i.e., see [65]. Also, in [66], the authors proposed a modeling approach that was AAS-based using ontologies to overcome the gap of semantic interoperability and allow efficient interactions between Industry 4.0.…”
Section: Related Workmentioning
confidence: 99%
“…As a result, one research direction shifted towards ontology development to capture domain knowledge and concepts to achieve this goal. Previously, we surveyed the scientific contributions of semantic AASs that used ontologies to model the Information and Communication layers of RAMI 4.0 in [12]. In that paper, we summarized the use cases and technologies used to develop different semantic AASs for the overall goal of improved data semantics and interopability within Industry 4.0.…”
Section: Ontologies For Industry 40mentioning
confidence: 99%